Mitral Valve Fenestration as a Rare Cause of Congenital Mitral Insufficiency Successfully Repaired - Moreira Neto,Francisco Fernandes (2021)
Abstract A rare case of congenital mitral insufficiency characterized by a fenestration in the anterior leaflet of mitral valve is reported. At operation, the mitral valve was successfully repaired by closure of unusual valvular tissue orifice with bovine pericardium and suture of the free edge between A1 and A2 without a ring annuloplasty.